Dicrostonyx hudsonius ... - Don E. Wilson; Russell A. Mittermeier; Thomas E. Lacher, Jr (Lynx Edicions, 2017)
35. Ungava Collared Lemming Dicrostonyx hudsonius French: Lemming d'Ungava / German: Ungava-Halsbandlemming / Spanish: Lemming de collar de Ungava Other common names: Labrador Collared Lemming Taxonomy. Mus hudsonius Pallas, 1778, [Labrador, Canada. This species is monotypic. Distribution. NE Canada, in N Quebec and Labrador, including Belcher and King George Is. Descriptive notes. Head—body 112-160 mm, tail 12-22 mm, hindfoot 20-25 mm; weight 40-90 g. The Ungava Collared Lemming is stocky, with relatively short limbs, short tail, small eyes, and indistinct dorsal stripe extending to rump. Pelage is seasonally dimorphic, with long white fur in winter to match snowy environments and brownish gray with buffy or rusty sides, throat, and ear tufts in summer. Venter is grayish. Poorly developed, reddish chest collar is often present. Habitat. Tundra from old beach terraces to alpine meadows up to elevations of c.1000 m. Near tree line, Ungava Collared Lemmings typically avoid wooded areas and inhabit burrows in ... : Published as part of Don E. Wilson, Russell A. Mittermeier & Thomas E. Lacher, Jr, 2017, Cricetidae, pp. 204-535 in Handbook of the Mammals of the World – Volume 7 Rodents II, Barcelona :Lynx Edicions on pages 297-298, DOI: 10.5281/zenodo.6707142 ...